Inconsistency in Constitutional Interpretation in The Judicial Review of The Anti-Corruption Law in Indonesia - Oktoriusman Halawa; Tomson Situmeang (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the dynamics of constitutional interpretation in the judicial review of Article 2 paragraph (1) and Article 3 of the Anti-Corruption Law, as well as to examine the obstacles and solutions in limiting state power in Indonesia. This research employs a normative legal method using statutory, case, and conceptual approaches. Legal materials are collected through library research and analyzed qualitatively using legal interpretation methods. The results show that the dynamics of constitutional interpretation in Case Number 142/PUU-XXII/2024 reflect a tension between a formalistic approach emphasizing legal certainty and a substantive approach oriented toward the effectiveness of anti-corruption efforts. The petition primarily concerns the application of norms rather than their constitutionality. Furthermore, the limitation of state power in Indonesia faces several challenges, including unclear institutional authority, inconsistent constitutional interpretation, political influence in law-making, and weak legal culture and integrity. From the perspectives of Gustav Radbruch and Carl J. Friedrich, a balance between legal certainty, justice, and utility, as well as the strengthening of constitutional mechanisms, is essential to ensure effective limitation of state power within a rule of law framework.